Effectiveness of combining patient follow-up with an educational intervention on self management skills of Type 2 Diabetes Mellitus patients: a primary care pragmatic trialcess: a single center survey analysis - ÇİFÇİLİ, SALİHA SERAP (My University, 2022)
Background: Self-management tools and programs have been developed to help Diabetes Mellitus (DM) patients manage their disease. However, these methods may not be very effective in patients with low health literacy. Research questions: Can a shared follow-up plan combined with education, facilitate patients’ diabetes self-management skills in primary care? Is this effect affected by patients’ current health literacy levels? Method: This is a non-randomized controlled clinical trial. We enrolled 84 Type 2 DM patients from three primary care centers in Istanbul, at least 40 participants being in the intervention (IG) and control groups (CG) (%80 power and %95 confidence level). A set of questions including patient characteristics, diabetes self-management scale and health literacy scale were used. Patients in the IG had three meetings with the researcher, in which, a \"DM Identity Card\" and a \"DM Diary\" developed by the researchers were given to the patients combined with an education session. The participants in the CG, were called by the researcher three times and briefly informed about DM. Diabetes self-management scale and health literacy scale were used. Results: The mean age of IG was 55,10(±8,40) and the CG was 59,51(±9,04). The participants of the both groups were predominantly female (IG: %58,5-CG: %60,5). After a three-months follow-up, the mean selfmanagement score of the IG increased from 65.53(SD=11,69) to 73.64(SD=11,50) (p<0,05), whereas the mean score of the CG increased from 57.3(SD=11,72) to 58.3(SD=9,36). No statistically significant relationship was found between the increase in self-management scores and the current health literacy of the participant (r=0,11 p>0,05). Conclusions: In conclusion, the follow-up method we developed with this study may increase the Type 2 DM patients’ selfmanagement skills regardless of the level of health literacy in primary care.
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Family Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEALTH CARE SCIENCES & SERVICES; MEDICINE, GENERAL & INTERNAL; Tıbbi Terminoloji; Tıbbi Sekreterlik ve Transkripsiyon; Sağlık Bilgi Yönetimi; Sağlık Meslekleri (çeşitli); Genel Sağlık Meslekleri; Gözden Geçirme ve Sınav Hazırlığı; Patofizyoloji; Liderlik ve Yönetim; Temel Bilgi ve Beceriler; Toplum Sağlığı ve Evde Bakım; Bakım Planlaması; Değerlendirme ve Teşhis; Dahiliye; Sağlık Politikaları; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Medical Terminology; Medical Assisting and Transcription; Health Information Management; Health Professions (miscellaneous); General Health Professions; Review and Exam Preparation; Pathophysiology; Leadership and Management; Fundamentals and Skills; Community and Home Care; Care Planning; Assessment and Diagnosis; Internal Medicine; Health Policy; Family Practice; Medicine (miscellaneous); General Medicine